Policy Capacity Pelaksanaan Peraturan Bersama Kepala Desa No. 2 Tahun 2022 Tentang Badan Usaha Milik Desa Bersama (BUMDESMA) - Endro Wahyudi; Erna Setijaningrum; Eko Supeno (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The Constitution No.6/2014 about villages, provides space and opportunities for two or more villages to collaborate in establishing Bumdes, as referred to as Bumdesma. The aim of this research is to describe and analyze the multidimensional perspective of policy capacity for Peraturan Bersama Kepala Kepala Desa Ngoro, Kauman, Rejoagung, Badang, Genukwatu, Jombok, Pulorejo, Banyuarang, Sidowarek, Gajah, Sugihwaras, Kesamben, and Kertorejo No. 2/2022 about Bumdesma Aria Sejahtera Ldk.. This study uses a qualitative method. The data collection techniques are observation, interviews and in-depth documentation. The analysis uses data condensation, data presentation, conclusions. This research uses the concept of policy capacity from Xun Wu, Howlett and Ramesh. The results of this research show that the Bumdesma can be said to be going well. Policy capacity in Bumdesma management efforts is the ability and resources used in implementing policies which include analytical capacity, operational capacity and political capacity at the individual, organizational and system levels. As an effort to increase policy capacity, Bumdesma needs to build a better information technology system, develop strategic planning, improve communication and coordination, and increase competitive and innovative human resources. The commitment of regional heads is also very necessary to support the existence of Bumdesma Ngoro District in proving research results and being able to provide recommendations that have an impact on the community.